Negotiating intergenerational relationships and social expectations in childhood in rural and urban Ethiopia. (August 2016) - Kassa, Sophia Chanyalew
Drawing on ethnographic fieldwork carried out in two socio-economically and geographically contrasting settings, this article reports on (a) how ideologies and valuations on childhood shape intergenerational relationships and (b) the ways in which expectations and responsibilities for children are negotiated between children and families in Ethiopia. Analysis of empirical data suggests that the intersection and implication of improved economic status and formal education are shifting values placed on children and are allowing new forms of child–parent interactions. Although children in urban and rural Ethiopia grow experiencing interdependent and dynamic relationships with parents (family), insights obtained reveal difference in what defines child–parent relationship and how it is negotiated. Affluent families aspire to maximize emotional satisfaction from what children achieve in school, whereas peasant families aim to ensure children contribute most to household well-being. This article argues that the act of being a child in urban affluent households reflects the socio-economic status of parents and the technical and material conditions in which children grow, whereas in rural peasant households, social, cultural and economic values vested on children inextricably shape how children should act. Insights obtained from the research reveal the fluid and complex practices of 'generationing' in Ethiopia and can help bridge the gap in understanding of how local familial and community ideologies and expectations of childhood are encountered by children and how children navigate expectations and intergenerational relationships.